2017
DOI: 10.1148/rg.2017160106
|View full text |Cite
|
Sign up to set email alerts
|

Enabling the Next-Generation Radiology Report: Description of Two New System Standards

Abstract: Currently, most radiology reports are highly variable and consist of unconstrained narrative text. This variability limits the ability to extract information from the report to guide clinical care, populate a data registry, or support quality improvement. This article introduces two newly available standards that pertain to radiology reports. Management of Radiology Reporting Templates (MRRT) is an integration profile that defines the format and exchange mechanisms for radiology report templates. Digital Imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
1
7
0
2
Order By: Relevance
“…A technical paper on Management of Radiology Report Templates (MRRT) illustrates the application of templates in the exchange of information in a clinical scenario of critical findings. Findings are coded to facilitate processing and automated notification of the referring physician [20]. Although the purpose and methodology differ from our study, we support the notion that technical solutions may improve efficiency and quality.…”
Section: Comparison With the Literaturesupporting
confidence: 66%
“…A technical paper on Management of Radiology Report Templates (MRRT) illustrates the application of templates in the exchange of information in a clinical scenario of critical findings. Findings are coded to facilitate processing and automated notification of the referring physician [20]. Although the purpose and methodology differ from our study, we support the notion that technical solutions may improve efficiency and quality.…”
Section: Comparison With the Literaturesupporting
confidence: 66%
“…The strengths of SR have been extensively demonstrated by the major scientific societies, which have supported several initiatives, aimed at promoting the diffusion of SR, including the creation of RSNA standardized templates, the translation of RSNA templates into European languages, and the ESR papers published on SR [ 21 , 22 ]. In this study, the panel of radiologists expert in abdominal imaging demonstrated a high degree of agreement regarding the definition of various points of the staging and restaging structured report.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, in adherence with the RSNA (Radiological Society of North America) and ESR structured reporting initiative, SIRM launched the Italian initiative aimed at creating a repository of structured reports, available to its members, to be used in clinical practice [15,16]. The initiative has been primarily focused on oncologic imaging, and a panel of experts, recruited from the SIRM study sections or chapters, has been set up.…”
Section: Methodsmentioning
confidence: 99%